EPISTIMOLOGI PENDIDIKAN ISLAM MENUJU PERSPEKTIF GENDER - Badriyah, Laila (Jurnal al Hikmah, 2017)
Education is one of the strategic means of transforming the culture that developed in the community. The discourse on gender is an interesting thing, both historically and todays modern realities. Islamic education epistimologi give space to women as